2020
DOI: 10.1159/000511402
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Extracellular Vesicles: An Intriguing Interplay

Abstract: <b><i>Background:</i></b> The outbreak of severe acute respiratory syndrome β-coronavirus 2 (SARS-CoV-2) has the potential to become a long-lasting global health crisis. The number of people infected with the novel coronavirus has surpassed 22 million globally, resulting in over 700,000 deaths with more than 15 million people having recovered (https://covid19.who.int). Enormous efforts are underway for rapid vaccine and treatment developments. Amongst the many ways of tackling the novel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 39 publications
0
53
0
2
Order By: Relevance
“…The immunogenic responses of exosomal S vaccine were boosted after the subsequent injection of AAV S vaccine (Kuate et al 2007). Based on this knowledge, exosomes from SARS-CoV-2 infected cells may induce similar immune responses (Elrashdy et al 2020b;Pocsfalvi et al 2020).…”
Section: Therapeutic Potentialmentioning
confidence: 99%
See 1 more Smart Citation
“…The immunogenic responses of exosomal S vaccine were boosted after the subsequent injection of AAV S vaccine (Kuate et al 2007). Based on this knowledge, exosomes from SARS-CoV-2 infected cells may induce similar immune responses (Elrashdy et al 2020b;Pocsfalvi et al 2020).…”
Section: Therapeutic Potentialmentioning
confidence: 99%
“…With these limitations in mind newer types of carriers have been devised. One at the forefront of development are extracellular vesicles (EVs) (O'Driscoll, 2020;Pocsfalvi et al 2020). They have gained considerable attention based on their natural biocompatibility and defined effectiveness as therapeutic and disease preventative agents in parallel microbial systems (Raposo and Stoorvogel, 2013;Pitt et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Endothelium contributes significantly to the circulating EVs in blood and lymph, and it is conceivable to propose that endothelium-derived EVs could be responsible for the dissemination of pro-coagulant and pro-inflammatory molecules that can perpetuate the dysfunction initiated in infected cells. Indeed, proteomic analysis of the EV in plasma of patients with different degrees of COVID-19 severity showed distinct protein signatures that correlate with clinical manifestations of the disease [ 184 ]. In a separate study, Barberis et al found that the proteome of the circulating EVs contained a large number of immune, pro-inflammatory and pro-coagulant proteins, and identified SARS-Cov-2 RNA in the exosomal cargo [ 185 ].…”
Section: The Biological and Clinical Relevance Of Endothelial Evs In Covid-19mentioning
confidence: 99%
“…The exchange of EVs between blood and lung can explain why intravenously administered EVs can influence lung physiology. Information on the mechanism of intercellular signaling by miRs and proteins contained in EVs are available in several reviews (e.g., [ 52 , 54 , 55 ]).…”
Section: Types Of Mscs and Msc-derived Productsmentioning
confidence: 99%